Development Of Animal Life Cycle Media Using Digital Comics For Fourth Grade Elementary School - Yuswantara, I Kadek Jodi; Margunayasa, I Gede; Wibawa, I Made Citra (International Journal of Elementary Education, 2021)
The covid-19 pandemic situation has limited availability of learning media for elementary school students. This research aims to develop animal life cycle media using digital comics for fourth-grade elementary school students. This research is a media development research using the ADDIE model. The pandemic situation causes research to be carried out until the development stage only. The subjects of this study were two material experts, two media experts, and two practitioners. The object of this study was the validity of animal life cycle media using digital comics. The analysis technique used is qualitative and quantitative analysis. The research data collection instrument was a rating scale questionnaire. The data obtained from the media validity test were analyzed to find the percentage score. The media test results obtained were the material expert test with 97.33%, the media expert test with 98%, and the practitioner test with 91%. The three test results got the predicate very well. It can be concluded that the animal life cycle media using digital comics is valid and suitable for use as a medium of learning in schools.